Image processing in Java / Kamal Firdausi Abd Razak - Abd Razak, Kamal Firdausi (1998)
The purpose of this project is to develop an image processing program using Java programming language. The focus is mainly on image enhancement process by using edge detection. The edge detection operator used is the Sobel operator. The Java interpreter used to develop the software is the Java Development Kit (JDK). This software can be used on any platform as long as it supports the Java environment. The entire presentation will be structured around a hierarchy of concepts of image processing starting from defining the terms of image, edge detection, and Java programming language. The results obtained are satisfactory and the program can be utilised in simple edge detection application.